2013
DOI: 10.1111/mmi.12465
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminal regions of YidC from Rhodopirellula baltica and Oceanicaulis alexandrii bind to ribosomes and partially substitute for SRP receptor function in Escherichia coli

Abstract: SummaryThe marine Gram-negative bacteria Rhodopirellula baltica and Oceanicaulis alexandrii have, in contrast to Escherichia coli, membrane insertases with extended positively charged C-terminal regions similar to the YidC homologues in mitochondria and Gram-positive bacteria. We have found that chimeric forms of E. coli YidC fused to the C-terminal YidC regions from the marine bacteria mediate binding of YidC to ribosomes and therefore may have a functional role for targeting a nascent protein to the membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 44 publications
5
40
0
Order By: Relevance
“…Although the SecYEG translocon overcomes this difficulty by forming a polypeptide-conducting channel that sequesters a translocating polypeptide from the lipidic environment (15)(16)(17), several lines of evidence (19,20,27), most notably the crystal structure of B. halodurans YidC2 (21), suggest that YidC uses a channel-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the SecYEG translocon overcomes this difficulty by forming a polypeptide-conducting channel that sequesters a translocating polypeptide from the lipidic environment (15)(16)(17), several lines of evidence (19,20,27), most notably the crystal structure of B. halodurans YidC2 (21), suggest that YidC uses a channel-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The pore can also open laterally to the lipid phase of the membrane, allowing release of a TM segment of substrates out of the translocon pore to establish membrane protein integration (15)(16)(17). Although earlier electron microscopic studies of Escherichia coli YidC and Saccharomyces cerevisiae Oxa1 led to a proposal that YidC forms a homodimer, which creates a channel-like structure at the subunit interface (18), more recent evidence suggests that a monomer of YidC interacts with the ribosome that is translating a membrane protein (19,20). The crystal structures of YidC from Bacillus halodurans at a resolution up to 2.4 Å (21) revealed that the five TM segments of YidC form a cavity presumably in the lipid bilayer.…”
mentioning
confidence: 99%
“…The YidC proteins from Gram-negative bacteria possess an additional TM helix and a large periplasmic region formed by the N-termini of the core TM region. Structural information about YidC has been limited to the crystal structures of the large periplasmic domain and electron-microscopic studies (Oliver & Paetzel, 2008;Ravaud et al, 2008;Kohler et al, 2009;Seitl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis highlighted the role of the C terminus of YidC in the ribosome binding but also suggested it to be not the sole determinant, so alternative ribosomal contacting sites were proposed within the positively charged C1 and C2 domains of YidC (25). The chimeric E. coli YidC with an extended C-terminal tail from Rhodopirellula baltica YidC (YidC-Rb) exhibited enhanced binding of translating ribosome forming primary interaction sites on the ribosomal rRNA helix 59 and the ribosomal protein L24, as shown by the cryo-electron microscopy structure of the YidC-Rb⅐RNC complex (26). Lately, Wickles et al (27) built a structural model of E. coli YidC via the intramolecular co-variation analysis, which appeared in agreement with the experimentally solved structure.…”
mentioning
confidence: 99%